International spillovers of ECB's unconventional monetary policy: The effect on Central and Eastern Europe - Klara Halova; Roman Horváth (Institut für Ost- und Südosteuropaforschung (IOS), 2015)
We examine how unconventional monetary policy of the European Central Bank influences macroeconomic stability in Central and Eastern European economies. We estimate various panel vector autoregressions using monthly data from 2008-2014. Using the shadow policy rate and central bank assets as measures of unconventional policies, we find that output and prices in Central and Eastern Europe temporarily increase following an expansionary unconventional monetary policy shock by the European Central Bank. Using both impulse responses and variance decompositions, we find that the effect of unconventional policies on output is much stronger than the effect on inflation. In addition, our results provide evidence that unconventional policy tends to reduce market uncertainty and domestic interest rates but that the effect on the real exchange rate is not significant.
urn:nbn:de:101:1-201603225140
Keywords: E52; E58; 330; unconventional monetary policy; ECB; Central and Eastern Europe; panel vector autoregression